Overcoming the incumbency and barriers to sustainable cooling. Issue 1 (22nd December 2022) - Lizana, Jesus; Miranda, Nicole D.; Gross, Larisa; Mazzone, Antonella; Cohen, Francois; Palafox-Alcantar, Giovani; Fahr, Patrick; Jani, Anant; Renaldi, Renaldi; McCulloch, Malcolm; Khosla, Radhika
This article examines cooling in the built environment, an area of rapidly rising energy demand and greenhouse gas emissions. Specifically, the status quo of cooling is assessed and proposals are made for how to advance towards sustainable cooling through five levers of change: social interactions, technology innovations, business models, governance and infrastructure design. Achieving sustainable cooling requires navigating the opportunities and barriers presented by the incumbent technology that currently dominates the way in which cooling is provided—the vapour-compression refrigerant technology (or air-conditioners). Air-conditioners remain the go-to solution for growing cooling demand, with other alternatives often overlooked. This incumbent technology has contributed to five barriers hindering the transition to sustainable cooling: (1) building policies based exclusively on energy efficiency; (2) a focus on temperature rather than other thermal comfort variables; (3) building-centric design of cooling systems instead of occupant-centric design; (4) businesses guided by product-only sales; and (5) lack of innovation beyond the standard operational phase of the incumbent technology. Opportunities and priority actions are identified for policymakers, cooling professionals, technicians and citizens to promote a transition towards sustainable cooling. Policy relevance: The priority actions that can overcome key barriers to a sustainable cooling pathway are as follows. (1) Moving building policies beyond energy efficiency to address climate mitigation and adaptation for improving the heat resilience of the built environment. Building indicators are needed to measure the passive survivability to heat. (2) Conventional cooling control and related regulations based exclusively on air temperature require expansion in scope to consider a wider range of thermal comfort variables, thus stimulating technological innovation. (3) Shifting building-centric cooling control to an occupant-centric design, downsizing centralised cooling requirements and enabling adaptive environments integrating personalised environmental control systems. (4) Business models moving from product-oriented to service-based businesses. (5) Environmental cooling considerations that address the humidity influence, the role of energy storage to support renewables through energy flexibility in cooling, and the impact of F-gases. Regulation and citizen empowerment through better environmental labelling can play an important role.